2016
DOI: 10.1161/hypertensionaha.115.06977
|View full text |Cite|
|
Sign up to set email alerts
|

Glucocorticoids Induce Nondipping Blood Pressure by Activating the Thiazide-Sensitive Cotransporter

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 45 publications
4
57
0
Order By: Relevance
“…This is also proven by the fact that beta-adrenoreceptor stimulation significantly participates in glucocorticoid excess-induced metabolic and gravimetric alterations (Kis et al, 2001;Kis and Crăciun, 2003 a, b). This experimental result is consistent with other similar research results, according to which the high amount of glucocorticoid is harmful, resulting in increased blood pressure (Hunter et al, 2016;Ivy et al, 2016;Jeje and Raji, 2017). In longterm treatment with glucocorticoids, increased blood pressure in the heart and vascular a b system disease can occur which change kidney function.…”
Section: Histological Studies Of the Kidney In The Control And Treatesupporting
confidence: 92%
See 2 more Smart Citations
“…This is also proven by the fact that beta-adrenoreceptor stimulation significantly participates in glucocorticoid excess-induced metabolic and gravimetric alterations (Kis et al, 2001;Kis and Crăciun, 2003 a, b). This experimental result is consistent with other similar research results, according to which the high amount of glucocorticoid is harmful, resulting in increased blood pressure (Hunter et al, 2016;Ivy et al, 2016;Jeje and Raji, 2017). In longterm treatment with glucocorticoids, increased blood pressure in the heart and vascular a b system disease can occur which change kidney function.…”
Section: Histological Studies Of the Kidney In The Control And Treatesupporting
confidence: 92%
“…Chronic corticosterone infusion increased bmal1, per1, sgk1, and tsc22d3 genes expression during the inactive phase. In the inactive phase pNCC was also elevated by corticosterone (Ivy et al, 2016).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, when examining NCC activation through phosphorylation (pNCC) by the WNK-OSR1/SPAK pathway [58], there appears to be a significant night/day difference in pNCC protein expression, with a peak at the beginning of the active period and a nadir at the start of the inactive period [57]. This night/day difference in pNCC expression was seen in another study as well [59]. Richards et al showed evidence that Per1 facilitates the expression of NCC through the WNK pathway, as reducing the expression of the clock protein resulted in a reduction of NCC, WNK1 and WNK4 as well [60].…”
Section: Circadian Rhythms Along the Nephronmentioning
confidence: 97%
“…This regulation of the circadian variation of plasma GC is controlled by the SCN through neural and humoral signals [111], however little is known about the effects of GC on circadian function in the kidney. A study by Ivy et al found that chronic corticosterone infusion led to increased levels of pNCC, Bmal1 and Per1 during the inactive phase, and a non-dipping BP phenotype [59]. Treatment of these mice with hydrochlorothiazide reversed the non-dipping phenotype back to normal [59].…”
Section: Integration Of Circadian Control Throughout the Nephronmentioning
confidence: 99%